Perancangan Prototype Game Edukasi "Petualangan Anak Sholeh" - Arfiani, ika (ScientiCO : Computer Science and Informatics Journal, 2020)
Submission of Islamic teaching materials in several schools and TPA / TPQ is made directly by way of delivery of content by teachers, and students pay attention, and then students can repeat. This is less effective in preparing children not to feel bored in learning. Therefore there is a need for multimedia applications that can provide lessons that can be repeated over and over again in any place. Multimedia applications that are packaged in the form of android-based educational games contain about the pillars of Islamic Pillars. The research method used is Research and Development (R&D), which is a process used to develop and validate educational products including potential and problems, data collection, product design, design validation, design revisions, product trials, product revisions, trial trials, product revisions, mass products. This research resulted in the prototype design of the application "SHOLEH CHILDREN ADVENTURE EDUCATION GAME." This will be further developed into a game application that can be used by students for learning and repetition of material related to Islamic pillars outside school hours.